Stereoselective Synthesis of Fluoroalkylated Butanolides - Erdbrink, Holger; Czekelius, Constantin (Synlett, 2013)
Starting from fluoroalkylated, optically active acyl oxazolidinones the corresponding di- and trisubstituted butanolides were prepared in enantiomerically pure form. Using a divergent synthetic route highly functionalized fluoroalkylated building blocks are accessible.
Keywords: fluorine; fluoroalkylation; lactones; stereoselective synthesis; chiral auxiliaries